Comparison of the professional activities of Slovak, Czech and Polish teachers at primary school level - Simoneta Babiaková (Czech Pedagogical Society, 2012)
The aim of the paper is to compare the professional activities of teachersfrom the three participating countries in terms of the time load. In the introduction,the author deals with the term "professiography" of teachers and focuses on thecontemporary professiographic research that, among other things, inspired thepresented international research into the teachers' professional activities. The nextpart of the paper describes the research objectives, strategy and methods. In thestudy, the author analyzes mainly activities that are directly related to the instructionand specifies the time the primary education teachers spent on them. Researchfindings show that the Czech teachers spend more time on preparing the instruction,assessing the pupils and correcting their work than their Slovak or Polish colleagues.The teachers from Slovakia allocate most of their time on explaining the instructionalcontent and the Polish teachers mostly motivate their pupils during the instruction and create individual plans for pupils with special needs. We also found that the timeload of primary education teachers in their profession is increasing when comparedto the past and apart from the activities directly or indirectly connected with teaching,they spend a lot of time on education and self-education brought by the changingsocial and professional conditions.